Livestock, ethics, quality of life and development in Latin America - Li Pun, H.H.; León Velarde, C.U.; Mares, V.M. (CAB International, 2000)
Latin America is well endowed with natural resources, yet poverty is wide-spread, wealth is distributed unequally and natural resoruces in marginal areas are deteriorating. The region can be broken down into several sub-regions according to geographic and ethnic characteristics, relative level of human Development and/or political organization. These differences must be recognized if efforts to solve common problems are to be targeted effectively. In spite of the region's relative wealth, nutritional deficits, especially in the consumption of calories and animal protein, are widespread. Problems of poverty, environmental degradation and equity are most acute in the Andean ecoregion and the tropical forest margins, especially in the rural areas. Livestock play a critical role in providing both food and non-food products for an ever-increasing population, and in ensuring the livelihood of impoverished smallholder farmers. Development of the livestock sector could help improve the economic and nutritional status of the poorest sectors of the population and promote equity and environmental protection. Many policies applied in the past have worked against these Development goals. This chapter provides examples of international and national policies that have had negative effects on livestock and rural Development and suggests ways in which policies and institutional arrangements might be improved. Development problems will be solved only through the application of better policies, the use of appropriate technologies and interinstitutional cooperation. Achieving this requires implementation of holistic and participatory approaches that link research and Development efforts. The aim of this chapter is to highlight some of the physical and socio-economic characteristics of the Latin American region; to discuss the economic, social and environmental importance of the livestock sector as a means of overcoming poverty, malnutrition and degradation of natural resources; to review ongoing economic and policy trends, how they affect the livestock sector and the implications for equity in access to resources, services and benefits; and to propose specific research and Development approaches to address some of the major economic, social and envrionmental challenges to livestock agriculture.